A case of severe leptospirosis with Jarisch–Herxheimer reaction presenting as respiratory failure - Shi, Yunzhen; Guo, Wanru; Hu, Ming; Wang, Yuxuan; Li, Jingnan; Hu, Wenjuan; Li, Xiaomeng; Xu, Kaijin (Frontiers in Public Health, 2023)
Background Leptospirosis is a widespread zoonotic disease caused by pathogenic Leptospira spp. The treatment of penicillin or tetracycline can cause a Jarisch–Herxheimer reaction (JHR), which can lead to acute respiratory distress syndrome (ARDS) and multi-organ failure in severe cases. The overall course of evolution and imaging features of a JHR exacerbation of leptospirosis have rarely been reported. Case presentation We present a case of leptospirosis complicated by pulmonary alveolar hemorrhage and a Jarisch-Herxheimer reaction (JHR) that required respiratory and vasopressor support. This case demonstrates a well-defined course of evolution of JHR and the imaging features. Conclusions Leptospirosis is easily misdiagnosed in some sporadic areas, and JHR complicates its management. Early diagnosis and appropriate treatment can reduce the mortality of severe leptospirosis with JHR.